FOREST FIRE GOVERNANCE AND REGIONAL ENVIRONMENTAL POLITICS IN SOUTHEAST ASIA: A BIBLIOMETRIC ANALYSIS - Wicaksono, Agung; Wardana, Data; Andry, Hendry; Maulana, Rio Yusri (JWP (Jurnal Wacana Politik), 2026)
Forest fires remain one of the most persistent environmental governance challenges in Southeast Asia, generating significant ecological, economic, social, and political consequences, including transboundary haze pollution. Despite the growing body of literature on forest fire management, a comprehensive understanding of the intellectual structure and development of forest fire governance research in the region remains limited. This study aims to map and analyze the evolution, thematic structure, collaboration patterns, and intellectual foundations of forest fire governance research in Southeast Asia using a bibliometric approach. Bibliographic data were collected from the Scopus database, resulting in a final dataset of 644 publications after applying systematic screening procedures. The analysis was conducted using VOSviewer, employing keyword co-occurrence, co-authorship, co-citation, and bibliographic coupling techniques. The findings reveal a substantial increase in scholarly attention to forest fire governance over time, reflecting the growing recognition of forest fires as complex socio-ecological and governance challenges. The thematic structure of the literature demonstrates a shift from predominantly ecological and technical perspectives toward governance-oriented approaches emphasizing institutional coordination, stakeholder collaboration, policy implementation, sustainability, and environmental management. Collaboration network analysis indicates that knowledge production remains concentrated among a limited number of countries and institutions, while regional scientific collaboration continues to exhibit fragmented patterns. The study further highlights the importance of state capacity, collaborative governance, and multi-level governance in addressing recurring forest fire crises and transboundary environmental problems. By integrating bibliometric mapping with governance-oriented interpretation, this study contributes to the literature on environmental governance, forest governance, and regional environmental politics in Southeast Asia while providing insights for policymakers seeking more adaptive and collaborative approaches to forest fire governance.